Riqueza de espécies e padrão horário e sazonal de capturas dos morcegos em fragmentos de floresta estacional semidecidual do alto rio Paraná, Brasil. - Ortêncio Filho, Henrique (2008)
In Brazil, about 25% of mammalian species belong to the order Chiroptera and the group is represented in all the territory. The present work aimed at investigating the specific richness and relative abundance, as well as the time and seasonal pattern of activity of bats in remnants of a stational semidecidual forest in high Paraná river, Brazil. The captures were performed monthly, between January and December, 2006, using 32 mist nets (8.0mx2.5m). To estimate the richness of species ACE, ICE, Chao1, Jack2 and Bootstrap estimators were used and to analyze the activity pattern, generalized linear models and Poisson distribution were used. The richness of bats was represented by 17 species and 563 individuals and the estimated richness curves showed a strong tendency to stability. Concerning activity patterns, among the larger frugivorous, Artibeus planirostris (Spix, 1823) A. lituratus (Olfers, 1818) and A. fimbriatus Gray, 1838, captures were verified during all the nocturnal period. As for smaller species, Platyrrhinus lineatus (E. Geoffroy, 1810), Carollia perspicillata (Linnaeus, 1758) and Sturnira lilium (E. Geoffroy, 1810), we noted the occurrence of peaks in the second and fourth hours. Related to seasonal pattern, a higher activity of bats during the summer was observed. The frugivorous [A. obscurus (Schinz, 1821), Phylostomus discolor Wagner, 1843, Chiroderma villosum Peters, 1860 and Pygoderma bilabiatum (Wagner, 1843)], the carnivorous Chrotopterus auritus Peters, 1865 and the insectivorous [Noctilio albiventris Desmarest, 1818, Lasiurus blossevillii (Lesson & Garnot, 1826), L. ega (Gervais, 1856) and Myotis nigricans (Schinz, 1821)] with low numbers of captures, were more active in the first hours of the night, whereas the hematophagus D. rotundus and the omnivorous P. hastatus were captured in different hours. Summer was marked by a higher number of captures due to the availability of resources. These results contribute to the knowledge of the group biology and suggest the need for implementing conservational strategies in order to keep the diversity of species, as well as changes in the activity pattern of bats in the region.